2015
DOI: 10.7763/ijcea.2015.v6.496
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Interaction between a New Mixture in Enhancing Drag Reduction Efficiency

Abstract: Abstract-Polymers are used as drag reducer in a strategic pipeline successfully for the past few decades due to its viscoelastic properties that can suppress the turbulent in pipelines. One of the many issues facing the use of these additives is its resistance to high shear forces during the transportation where it can be easily degraded where they pass them a pump. In the present work, polymer-surfactant complexes of anionic polymer and nonionic surfactant are investigated to prove its capability in enhancing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Different complex concentrations were prepared using five concentrations of polymer (i.e., 50, 100, 150, 200, and 300 ppm) and surfactant (i.e., 200, 400, 600, 800, and 1000 ppm). The procedure adopted by Bari et al [35] was followed in the current study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different complex concentrations were prepared using five concentrations of polymer (i.e., 50, 100, 150, 200, and 300 ppm) and surfactant (i.e., 200, 400, 600, 800, and 1000 ppm). The procedure adopted by Bari et al [35] was followed in the current study.…”
Section: Methodsmentioning
confidence: 99%
“…Different complex mixtures have been used recently as DRAs in pipelines [24,30,31] and rotating disk apparatus [32][33][34][35]. Mohsenipour et al [24] studied the interaction between an anionic copolymer, which comprises acrylamide and sodium acrylate (referred to as PAM) and cationic surfactant of octadecyltrimethylammonium chloride (OTAC), in pipeline flow.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that micro-grooved disks exhibit significant drag reduction effects. Bari et al [13] investigated the complex of anionic polymers and non-ionic surfactants and demonstrated their capability to enhance drag reduction and mechanistic degradation performance.…”
Section: Introductionmentioning
confidence: 99%
“…Huang [9] pointed that an inter-entangled network of polymers existed when using the solutions of polyethylene oxide and carboxymethyl cellulose which exhibits some improvement in reducing pressure drop. Arthurs [10] exploited an interaction between anionic copolymer of poly(acrylamide-codiallyl dimethylammonium chloride) and nonionic surfactant (tween 20) for producing better DRA performance and mechanical stability in aqueous media. Dia et al [11] pointed out using a mixture of non-ionic polyolefins, cetyl trimethyl ammonium bromide as a cationic surfactant, and salt of sodium salicylate as its counter-ion in diesel can reduce the pressure drop to 40%.…”
Section: Introductionmentioning
confidence: 99%